The klap-trap: A device to monitor dynamics of the klap mechanism in speed skating - Maw, S.; Johnston, C. R.; Yuen, A. (The Engineering of Sport 6, Volume 3 Developments for Innovation, 2006)
An electromechanical system has been designed and built to measure the kinematics of the klapskate mechanics in spped skating. A string potentiometer was used to determine the opening and closing dynamics of a klap mechanism during actual speed skating at the Calgary Olympic Oval. Custom designed and fabricated clamps were used to attach the potentiometer to the klapskate mechanism. A preliminary study was conducted on four speed skaters. Klap dynamics were distinguishable based on skater fatigue levels, the location of the skater on the track and effort level of the subject. Parameters analyzed were maximum klap opening, stride frequency, and klap opening and closing timing. The opening angle of the klap mechanism was found to increase with increased effort and was higher in straights than corners. The result indicated that the concept proposed can measure the dynamics of the klapskate and may be an important training tool.